Diagnostico turístico del Museo Municipal del cantón Babahoyo - Torres Encalada, Alexandra Elizabeth (2023)
This case study is carried out with the purpose of carrying out a Tourist Diagnosis of the Municipal Museum of the Babahoyo Canton where the research question was raised: What is the current situation and its potential of the Babahoyo museum? Regarding the objectives as a general objective, the following was designed: Diagnose the current tourist state of the city museum in order to know the potential of the tourist attraction of the canton. The methodology used in the work established the mixed research approach because qualitative and quantitative research techniques were used since the survey technique was used, which was applied to the residents of the Babahoyo canton and an observation sheet where the survey was carried out. Information from the Municipal Museum of the Babahoyo Canton. Once the information was collected, the main results were that the museum is administered by the Municipal Gad and is in constant care to maintain the conservation of the Historical cultural resources that they have preserved since their aboriginal times. Another result to highlight is that despite the fact that 48.2% of people DO know about the existence of the museum in Babahoyo, 77.9% have not visited it. However, 58.6% indicate that they would like to visit the Municipal Museum of the canton.